Dauru Wasail Attawasul Alijtima’i Fi Ta’lim Allughah Al’arabiyyah - Qasim, Muhammad Qasim Kh.A; Tabrani, Ach (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2024)
Social media is important in education, especially in teaching the Arabic language. This research aims to know social media, its role in teaching the Arabic language, and its advantages and disadvantages. The method used in this research is the descriptive method with a qualitative approach, and data is collected by reviewing books, articles, periodicals, the Internet, etc., then analyzing, discussing, and drawing conclusions. The results of this research are: 1) some social media can be used in teaching the Arabic language, such as YouTube, Facebook, and WhatsApp. 2) These social media have a role in teaching the Arabic language as they make lessons more efficient. 3) Using these means in teaching Arabic has pros and cons. The teacher is the primary supervisor of the learning process and it is his responsibility to guide the students and advise them on the best ways and means that will help them in their learning